Reframing the EU budget decision-making process - Indhira Santos; Susanne Neheider (Bruegel, 2009)
The EU budget review process will restart as we approach the end of the current financial framework 2007-2013. This paper traces the history of the EU budget and draws lessons for the review to come. Whatever reforms are proposed, they must serve to shift spending to policy areas and instruments where the EU can best add value while at the same time recognising the political need for member states to present EU budget negotiation results in `net-balance' terms. A two-stage negotiation is proposed: first member states should negotiate and agree on what constitute EU public goods, to be financed in proportion to GNI shares. Everything else would thereafter - by default - be deemed redistributive/compensatory spending to be financed, at least at the start, on the basis of member states' current overall net balances.
Keywords: 330; Öffentlicher Haushalt; Haushaltsplanung; Politische Entscheidung; Öffentliche Ausgaben; Öffentliche Güter; EU-Staaten